Navigating the evolving landscape of colorectal cancer screening with a practical framework: a comprehensive analysis of existing and emerging technologies for informed decision-making - Sapienza, Michael; Davis, Cheryl; Boudes, Mathieu (Oncology Reviews, 2025)
The colorectal cancer (CRC) screening landscape has rapidly evolved, introducing new technologies alongside established methods. The lack of head-to-head observational studies comparing these diverse options impairs clinicians’ and patients’ ability to make informed choices in CRC screening test selection. This manuscript aims to provide a comprehensive review of existing and emerging CRC screening technologies and develop a practical framework for informed decision-making. We conducted a systematic review of current literature on CRC screening methods, including colonoscopy, fecal immunochemical test (FIT), multi-target stool DNA test (mt-sDNA), the next-generation multi-target stool DNA test, multi-target stool RNA test (mt-sRNA), and blood-based tests. We summarized performance characteristics, adherence rates, follow-up colonoscopy rates, accessibility, and costs for each method. Our review revealed significant variations in test performance, patient adherence, and implementation factors across screening modalities. Blood-based tests showed promise in terms of patient acceptance but currently have lower sensitivity for early-stage cancers with a higher participant adherence when screening navigation is provided. Our review led to the development of a comprehensive framework for evaluating CRC screening options, addressing the critical need for informed decision-making in this area. The framework encompasses five key dimensions: test performance (sensitivity and specificity for CRC and precancerous lesions), patient considerations (invasiveness, preparation, and location preferences), adherence and follow-up (real-world rates and diagnostic colonoscopy completion rates), accessibility and cost (insurance coverage, out-of-pocket expenses, and system integration), and screening interval (recommended frequency and long-term impact). By synthesizing data, the framework enables healthcare providers and patients to navigate the complex landscape of screening options, facilitating personalized recommendations tailored to individual risk factors, preferences, and healthcare system constraints. Future research should validate this framework in diverse clinical settings and update it as new technologies emerge, ensuring continued improvement in CRC screening participation, effectiveness, and outcomes.